MENINGKATKAN MINAT MEMBACA SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK DENGAN METODE SQ3R (Survey,Question,Read,Recite,Review) - Dwi Pujirahayu Puji; Ali Rachman; Sulistiyana (JCOSE Jurnal Bimbingan dan Konseling, 2022)
The purpose of this study is to increase students' interest in reading through group guidance services using the SQ3R (Survey, Question, Read, Recite, Review) students in class XI IPS at SMAN 1 Martapura.This research uses the type of guidance and counseling research (PTBK) using qualitative research methods and is carried out in two cycles. The sample of this study were students of class XI IPS, totaling 6 students. The sampling technique used is purposive sampling. The data instrument used was an observation sheet with an assessment rubric, seen from the indicators of the success of the researcher's activities, student activities and increasing student interest in reading.The results of this study indicate an increase in each cycle, for research activities to reach the "good" criteria for student activities to reach the "active" criteria and to increase students' reading interest through group guidance services using the SQ3R method to achieve the "increasing" criteria. The conclusion of this study is that group guidance services with the SQ3R method (Survey, Question, Read, Recite, Review) can increase students' reading interest.